ANALYSIS OF THE INFLUENCE OF AUDIT OPINION AND PROFITABILITY ON AUDIT REPORT LAG IN MANUFACTURING COMPANIES - Sitanggang, Eva Rianty; Bachtiar, Lasman Eddy; Sihotang, Elsa Theodora Valentina (KRISNA: Kumpulan Riset Akuntansi, 2026)
The competitive capital market encourages companies to accelerate the issuance of audited financial statements. This study aims to analyze the effect of audit opinion and profitability on audit report lag in manufacturing companies in the basic and chemical industries, listed on the Indonesia Stock Exchange (IDX), in 2023. The method employed is a quantitative approach, utilizing multiple linear regression analysis. The results showed that the audit opinion had a significant effect on the audit report lag with a significant value of 0.004 and a t-count of 10.042. On the other hand, profitability did not have a significant influence on the audit report lag, with a significant value of 0.557 and a t-count of 0.593. The F test shows that audit opinion and profitability simultaneously affect the audit report lag with a significant value of 0.000. However, the determination coefficient (R²) test showed that these two variables only contributed 1.1% to audit report lag, while 98.9% was influenced by other factors not studied in this study.